Post-traumatic condylar hyperplasia and temporomandibular joint ankylosis in a single patient: a case report based on cone beam computed tomography images - Fatimah, Tati Siti; Jamaluddin, Rafiqah Rezky Amelia; Epsilawati, Lusi (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2026)
Objectives: This case report aims to provide information about post-traumatic condylar hyperplasia and temporomandibular joint ankylosis, and its features on CBCT imaging. Case Report: A 16-year-old female patient visited the Radiology Installation of RSGM Universitas Padjadjaran with a referral for CBCT TMJ scan, prompted by a chief complaint of restricted mouth opening. The patient had a history of a traffic accident two years prior, resulting in multiple facial fractures that were treated through several surgical interventions. CBCT images showed morphological irregularities and enlargement of both right and left condyles, glenoid fossae, and articular eminences. Moreover, the development of fibrous tissue was observed within the joint space, accompanied by bone fusion. Conclusion: Condylar hyperplasia and temporomandibular joint ankylosis are pathological conditions that can arise as a consequence of trauma to the facial region. This case highlights the importance of radiological evaluation in identifying morphological alterations of the temporomandibular joint complex, such as condylar enlargement, joint space obliteration, and fibrous or bony fusion. These conditions significantly impact the function of the stomatognathic system, emphasizing the necessity for prompt intervention. Early recognition of these radiographic features is essential to support accurate diagnosis, guide appropriate clinical management, and prevent further deterioration of mandibular function.